PENERAPAN MODEL BERMAIN PERAN UNTUK MENINGKATKAN KETERAMPILAN SOSIAL DAN KEMAMPUAN BERBICARA ANAK USIA DINI - Gustin Maripi (UNIB Press, 2023)
The purpose of this study was to describe the application of the role-playing model to improve children's social skills and speaking skills and to know its effectiveness compared to the model used by teachers in group B at Pembina Tais Pembina State Kindergarten. This type of research uses a combination of Classroom Action Research (CAR) with quasi-experimental. This is done for the purpose of broadening and deepening understanding of the conditions that occur in the field. In this research, the research design is Sequential Exploratory Design. The tool used in data collection is an observation sheet. The results of the classroom action research showed that there was an increase in children's social skills and speaking skills between cycles. The application of the role play model is effective in improving children's social skills and speaking skills. The implication of this study is that teachers can try to apply role-playing models as a daily learning method, especially in early childhood learning group B. The results of this study recommend that teachers should prefer learning models and methods as well as learning media that can improve aspects of learning. aspects of child development